Have a good trip! expanding our concepts of the quality of everyday travelling with flow theory. Issue 4 (2nd October 2022) - Te Brömmelstroet, Marco; Nikolaeva, Anna; Mladenović, Milos; Milakis, Dimitris; Ferreira, Antonio; Verlinghieri, Ersilia; Cadima, Catarina; de Abreu e Silva, Joao; Papa, Enrica
ABSTRACT: The dominant tradition in transport planning and policy practice considers travel as a derived activity and travel time as an economic disutility. A growing body of literature is challenging this perspective, demonstrating that being 'on the move' is a rich experience interlaced with profound shared and individual meanings that can have positive implications on quality of life, well-being and personal development. Yet, mobility in general, and commuting in particular, is often reported as one of the least pleasant daily experiences and as a source of massive environmental impacts. This exploratory article hypothesizes that flow theory, based on Csikszentmihalyi´s seminal work on optimal states of consciousness, has the potential to offer important insights that can contribute to research and policy action on achieving both sustainable and satisfying forms of daily mobility. The article draws on an online exploratory questionnaire in order to reflect on flow theory in relation to the capacity of different mobility modes to either facilitate or constrain the occurrence and duration of optimal states of consciousness. Preliminary conclusions provide a basis for outlining a set of future research directions aimed at better understanding mobility experiences and their relationships with flow theory.